Elevation of IgE in patients with psoriasis: Is it a paradoxical phenomenon? - Shi, Leyao; Liu, Chen; Xiong, Huabao; Shi, Dongmei (Frontiers in Medicine, 2022)
Immunoglobulin E (IgE) is one of the immunoglobulins secreted by plasma cells in the lamina propria of the nasopharynx, tonsils, bronchi, and gastrointestinal mucosa. It is the primary antibody involved in the development of atopic dermatitis (AD). The pathogenesis of AD is usually associated with high levels of IL-4 and IL-13 produced by T helper 2 (Th2) cells as well as with high levels of IgE. While psoriasis is a disease driven mainly by Th17 cells and the related IL-17 pathological effects. Although these immune-pathological differences lead to two clinically distinct diseases, interestingly, some psoriasis patients are also present with AD-like manifestations such as high levels of IgE and pruritus. However, the reason that AD and psoriasis can share high levels of IgE remains to be fully clarified. It is plausible to hypothesize that psoriasis and AD may share common pathogenesis at some point of the disease spectrum, since the effective T cells still hold plasticity and can re-differentiate upon inherent and environmental factors. Among them, IgE may represent an important indicator of this phenomenon, highlighting the importance of IgE as a key link in the developments of both AD and psoriasis.